2010
DOI: 10.3892/or_00001036
|View full text |Cite
|
Sign up to set email alerts
|

The proliferation marker Chromatin Assembly Factor-1 is of clinical value in predicting the biological behaviour of salivary gland tumours

Abstract: Abstract. Salivary gland tumours (SGT) constitute a diagnostically challenging group of neoplasms with frequently unpredictable clinical outcome. The proliferation rate facilitates the identification of aggressive SGT. The Chromatin Assembly Factor-1 (CAF-1) is a major epigenetic regulator of nuclear chromatin organization during DNA replication. It plays a critical function in human tumourigenesis and has been proposed as a new proliferation and prognostic marker for some malignancies. This study focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…In fact, several recent reports have highlighted the strict relationship between CAF-1/p60 over-expression and adverse behaviour of different malignant tumours, including prostate, tongue, salivary glands carcinomas and cutaneous melanoma 28 - 31 . These studies have confirmed the hypothesis that CAF-1/p60 is heavily involved in tumoural and metastatic processes, constituting an independent prognostic biomarker of tumour evolution 8 25 32 - 34 .…”
Section: Discussionmentioning
confidence: 71%
“…In fact, several recent reports have highlighted the strict relationship between CAF-1/p60 over-expression and adverse behaviour of different malignant tumours, including prostate, tongue, salivary glands carcinomas and cutaneous melanoma 28 - 31 . These studies have confirmed the hypothesis that CAF-1/p60 is heavily involved in tumoural and metastatic processes, constituting an independent prognostic biomarker of tumour evolution 8 25 32 - 34 .…”
Section: Discussionmentioning
confidence: 71%
“…A histone chaperone, chromatin assembly factor-1 (CAF-1), acts as an epigenetic regulator of nuclear chromatin organization during DNA replication. CAF-1 is composed of subunits p150, p60 and p48, with concomitant overexpression of p60 and down regulation of p150 correlated with clinicopathological profile indicating advanced stages, local recurrence, metastasis, overall survival, thus enables prognosis in oral cancer patients [106,107]. The data emphasizes the complex mechanisms with genetic and epigenetic regulation playing a critical role in oral carcinogenesis.…”
Section: Histone Modifications In Oral Cancermentioning
confidence: 90%
“…For each case, double immunolabelling of routine tissue sections and corresponding tissue microarrays (TMAs) was performed with the EnVision ™ G/2 Doublestain System (Dako, Carpinteria, CA, USA) 45,46 . Immunohistochemistry was carried out as previously described 32–35,47 . Briefly, sections were heated at 55°C for 60 min, deparaffinized, and processed for antigen retrieval by microwaving in 1% sodium citrate buffer, pH 6.0.…”
Section: Methodsmentioning
confidence: 99%
“…Knocking down p60 disrupts the activity of CAF‐1 in nucleosome assembly, causing replication fork arrest, activation of the intra‐S‐phase checkpoint, and global defects in chromatin structure 28–31 . The nuclear expression of CAF‐1/p60 is increased in multiple types of cancer, proportionally to their adverse clinical behaviour 23,31–34 . On account of these postulates, we examined the expression of the stem cell‐associated antigens CD133, CD166, CD44 with the v6 variant and nestin (frequently associated with CSCs of solid malignancies) in a series of primary and metastatic OSCCs 35 .…”
Section: Introductionmentioning
confidence: 99%